Declining Procedures by Pediatric Critical Care Medicine Fellowship Trainees - Engorn, Branden M.; Newth, Christopher J. L.; Klein, Margaret J.; Bragg, Elizabeth A.; Margolis, Rebecca D.; Ross, Patrick A. (Frontiers in Pediatrics, 2018)
Background: Pediatric Critical Care Medicine Fellowship trainees need to acquire skills to perform procedures. Over the last several years there have been advances that allowed for less invasive forms of interventions. Objective: Our hypothesis was that over the past decade the rate of procedures performed by Pediatric Critical Care Medicine Fellowship trainees decreased. Methods: Retrospective review at a single institution, tertiary, academic, children’s hospital of patients admitted from July 1, 2007 – June 30, 2017 to the Pediatric Intensive Care Unit and Cardiothoracic Intensive Care Unit. A Poisson regression model with a scale adjustment for over-dispersion estimated by the square root of Pearson's Chi-Square/DOF was applied. Results: There has been a statistically significant decrease in the average rate of central venous lines (p=0.004; -5.72; 95% CI: -9.45, -1.82) and arterial lines (p=0.02; -7.8; 95% CI: -13.90, -1.25) per Fellow per years in Fellowship over the last 10 years. There was no difference in the rate of intubations per Fellow per years in Fellowship (p=0.27; 1.86; 95% CI: -1.38, 5.24). Conclusions: There has been a statistically significant decrease in the rate of central venous lines and arterial lines performed by Pediatric Critical Care Medicine Fellowship trainees per number of years in Fellowship over the last 10 years. Educators need to be constantly reassessing the clinical landscape in an effort to make sure that trainees are receiving adequate educational experiences as this has the potential for an impact on the education of trainees and the safety of the patients that they care for.